The worlds of wine: Old, new and ancient - Hua Li; Hua Wang; Huanmei Li; Steve Goodman; Paul VanderLee; Zhimin Xu; Alessio Fortunato; Ping Yang (Wine Economics and Policy, 2018)
As the world's seventh largest wine producer (OIV, 2017), China plays a significant role in the world's wine industry. Classified as neither New or Old World it was recently classified into a "New, New World Category" (CNCCEF, 2009 Lawrence, 2016). This paper presents an overview of the Chinese wine industry using evidence from literature of archaeological finds and documents to propose a new category extending the New or Old World definitions. We propose classification of the Chinese wine industry as Ancient World, a term which might also be useful in other producing nations such as Greece and Georgia.
Keywords: 330; Ancient World; China; New World; Old World; Wine